THE ACCURACY OF SENTENCE LEVEL IN ENGLISHINDONESIAN SUBTITLE OF ‘THE END OF THE F***ING WORLD – SEASON 2 - Akmala Ashlikhatina; Januarius Mujiyanto (Universitas Negeri Manado, 2021)
This study attempts to find the accuracy of sentence level ((1) simple sentence, (2) compound sentence, (3) complex sentence, (4) compound-complex sentence) in English-Indonesian subtitle of The End of the F***ing World – Season 2. The researcher collected the data by watching the series in English and Indonesian subtitle, then these subtitle were categorized into those 4 types of sentences. These data were checked its accuracy using a theory from Nababan et al. (2012). The researcher found 461 data of simple sentences and 445 (96.7%) of them are accurate. Second one, the researcher found 67 data of compound sentences and 63 (94%) of them are accurate. Third one, the researcher found 43 data of complex sentences and 41 (95%) of them are accurate. Last one, the researcher found 8 data of compound-complex sentences and 7 (87.5%) of them are accurate. Based on that, the researcher can say that the subtitle is accurate, but I still found some mistakes that are considered as major ones because these might cause ambiguity or misunderstanding to audiences, that’s why we – as the audiences – also need to be more careful in reading some subtitle.